2013
DOI: 10.1080/03079457.2013.788129
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, presence of integrons and biofilm formation ofSalmonellaPullorum isolates from eastern China (1962–2010)

Abstract: Three hundred and thirty-seven isolates of Salmonella Pullorum from eastern China between 1962 and 2010 were characterized for antimicrobial susceptibility (disk diffusion method), the presence of integrons (polymerase chain reaction followed by sequencing) and the ability to form biofilms (semi-quantitative adherence assay). Two hundred and fifty-eight isolates (76.6%) exhibited multiple drug resistance (MDR; resistant to at least three different classes of antimicrobials), and the level of drug resistance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
3
25
2
4
Order By: Relevance
“…Previous publications showed that pullorum disease infection rates in China were usually over 30% (30), which was different from what has been reported in developed countries (31). For a long time the prevention and control of pullorum disease in China have mainly depended on the use of antibiotics, leading to a high level of drug-resistant bacteria (32), and this made the prevention and control a great challenge. Recently, the official document on the National Medium and LongTerm Planning for Prevention and Control of Animal Epidemics (2012-2020) was issued in China (33), in which the government outlined plans to control pullorum disease through the detection and purification through a medium-or long-term program.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous publications showed that pullorum disease infection rates in China were usually over 30% (30), which was different from what has been reported in developed countries (31). For a long time the prevention and control of pullorum disease in China have mainly depended on the use of antibiotics, leading to a high level of drug-resistant bacteria (32), and this made the prevention and control a great challenge. Recently, the official document on the National Medium and LongTerm Planning for Prevention and Control of Animal Epidemics (2012-2020) was issued in China (33), in which the government outlined plans to control pullorum disease through the detection and purification through a medium-or long-term program.…”
Section: Discussioncontrasting
confidence: 42%
“…These three areas are also the main producers of animal-derived foods in China; in 2012, their output of meat, eggs, and milk accounted for 19.14%, 19.45%, and 9.17% of total Chinese production, respectively (China Agriculture Statistical Report, 2012). Previous studies documented a phenotype for Salmonella serovars that was discovered in chickens and pigs, and in animal-derived foods, in China (Gong et al, 2013; Li et al, 2013; Lai et al, 2014; Wang et al, 2014). However, specific knowledge of the Salmonella serovars that exist in dairy cows and other farm animals in central China is currently lacking.…”
Section: Introductionmentioning
confidence: 98%
“…However, since the early 1990s, antimicrobial- and multidrug-resistant Salmonella strains have emerged, leading to treatment failure. Researchers have reported a link between the use of antimicrobials in food animals and the emergence of antimicrobial resistance in pathogenic bacteria (Gong et al, 2013). Multidrug-resistant bacteria pose a severe threat to public health, particularly those that are resistant to β-lactams and fluoroquinolones (Lai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Global Monitoring data showed an overall increase of antibiotic resistance in Salmonella although there are a large geographical variability and serotype (Parry and Threlfall, 2008;Gong et al, 2013;European Centre for Disease Prevention and Control, 2013;Lai et al, 2014;Russel et al, 2014;Andino and Hanning, 2015). It is urgent to develop a broader understanding of Salmonella infection in animals and humans (Kuang et al, 2015) to guide research towards discovering alternatives to current antibiotics.…”
Section: Epidemiology Of Salmonella Spp Worldwidementioning
confidence: 99%